Dysregulation of microRNAs and renin-angiotensin system in high salt diet-induced cardiac dysfunction in uninephrectomized rats - Amara, Venkateswara Rao; Surapaneni, Sunil Kumar; Tikoo, Kulbhushan (PLOS ONE, 2017)
Uninephrectomy is not associated with major adverse events in cardiovascular and renal functions of live kidney donors. The effect of high salt diet on the quality of life of live kidney donors is largely unknown. Hence in this study, we aimed to determine the effect of high salt diet on the alterations of renin-angiotensin system and microRNAs leading to CV and renal dysfunction in uninephrectomized rats. In order to mimic clinical scenario, uninephrectomized male Sprague Dawley rats were fed initially with normal pellet diet for 12 weeks and then for 20 weeks with high salt (10% w/w NaCl) diet. At the end of the study, biochemical, functional, histological and molecular parameters were measured. High salt diet feeding resulted in renal dysfunction & fibrosis, decreased baroreflex sensitivity, increased in vivo cardiovascular reactivity to angiotensin II owing to upregulation of angiotensin II type 1 receptors and L-type calcium channels leading to cardiovascular dysfunction in uninephrectomized rats (UNX+HSD) worse than that of normal (binephric) rats fed with high salt diet (HSD). Protein expression of functional and hypertrophic protein markers revealed decreased SERCA, p-AMPK and increased p-AKT. Interestingly, levels of miR-25, miR-451 and miR-155 increased and miR-99 decreased in heart of uninephrectomized rats fed with high salt. However, circulating miR-25 and miR-451 levels decreased and miR-99b increased in these animals. Our study points out that since tissue and circulating levels of miRNAs are not similar, caution must be exercised during the usage of miRs as diagnostic or prognostic biomarkers. To our knowledge, we are the first to show that epigenetic alterations result in cardiac dysfunction in uninephrectomized rats fed with high salt diet.